OCCUPATION IN THE VITAL REGISTRATION SYSTEM - Costa, Letícia B. (1985)
The author discusses the results of an analysis of the information on occupation, collected during the last few decades in connection with vital events in the State of São Paulo (Brazil). The stages of collection, clearing, coding and processing are considered, and the resulting tables are investigated. The evidence suggests that no historical series is available, as far as occupation is concerned. It is suggested that historical series be initiated, based on the Brazilian Classification of Occupations (CBO) , which has been in use since 1977 for the coding of deaths. The suggestions follow two lines: a) the separation of the labor force from the inactive population, through the creation of new codes to describe the various groups of inactives; b) the introduction of another set of new codes referring to occupations that cannot be described in detail, but contain some information worth preserving.